Gender stereotypes in the angel investment process. Issue 2 (11th June 2018) - Edelman, Linda F.; Donnelly, Róisín; Manolova, Tatiana; Brush, Candida G.
Abstract : Purpose: Women-led companies receive less than 5 per cent of early-stage equity investment. This paper aims to explore the disparity in equity funding between men- and women-led companies, using a social identity perspective, complemented by insights from signaling theory. We argue that in the angel group context, which is male-dominated, gender stereotypes may bias angels' interpretation of the signals sent by entrepreneurs, so that entrepreneurial ventures led by men are more favorably evaluated, thus excluding women entrepreneurs from funding. The ideas are tested on a sample of 358 entrepreneurs who applied for funding from a northeast US angel group using perceptual data from both sides of the investment dyad. Findings suggest that angel investors view women-led entrepreneurial ventures as having less legitimacy, even though we see no difference in actual legitimacy across ventures. Design/methodology/approach: The ideas are tested on a sample of 358 entrepreneurs who applied for funding from a northeast angel group using perceptual data from both sides of the investment dyad. Findings: The findings suggest that, in the context of angel investing, there is a subtle bias that follows from the perceived stereotype between being female and the ability to lead a legitimate new venture. Thus, this study tests the tenets of the social identity theory by finding that mostly male angel investors act in accordance to their gender prescribed roles when they evaluate businesses presented by women entrepreneurs providing some evidence of "in-group" and "out-group" effects and stereotypes. Research limitations/implications: The findings continue the conversation about biases toward women in early-stage financing by using a social identity lens to look at the way in which adopted identities lead to particular outcomes and stereotypes. The authors have used the context of angel investing to test these ideas, finding some support for their contention that gender is pivotal when angels are making investment decisions. For researchers, this study suggests that gender should not be used solely as a control variable, but instead should be the focus of the inquiry itself. Practical implications: For practitioners, this study reminds women seeking angel investment that they are not playing on a level field and so they should do all that they can to enhance the legitimacy of themselves and their ventures. Originality/value: The authors contend that within an angel group that is composed of predominantly men, role stereotypes of entrepreneurs as masculine will be expected, therefore creating gender biases against women. The authors expect these biases, whether conscious or unconscious, will lead the angel investors to evaluate men entrepreneurs more favorably than women entrepreneurs as they move through the angel investment process. Therefore, for women entrepreneurs in the early stages of investment funding, the authors posit that the dearth of funding is a function of gender identity stereotypes which may be manifested in hidden and often unconscious biases on the part of the angel investor.